STUDY ON QUANTITATIVE ANLAYSIS OF TWO IMPORTANT MEDICINAL PLANTS GLORIOSA SUPERBA L. AND CELASTRUS PANDICULATES WILDLIFE (International Journal of Food and Nutritional Sciences, 2022)
Gloriosa superba L., a perennial herb from the Colchicaceae family, and Celastrus paniculatus Wild, an evergreen climbing shrub, are two plants of significant medicinal value. Both are integral to traditional Indian medicinal systems like Ayurveda, Unani, and Siddha. The research paper aims to highlight the nootropic activity of C. paniculatus while exploring its phytochemistry, traditional uses, and other pharmacological activities. Both Gloriosa superba L. and Celastrus paniculatus Wild exemplify the importance of traditional medicinal plants, not just in historical practices, but also in modern pharmacology. The rich phytochemical profiles and broad therapeutic potential of these plants call for continued research and exploration. This study underscore the need for the further integration of these natural resources into modern medicinal practices.